2010
DOI: 10.1002/elan.201000521
|View full text |Cite|
|
Sign up to set email alerts
|

The Electrochemical Behavior of Gold Nanoparticle‐Tantalum(V) Phthalocyanine Composites: Applications Towards the Electroanalysis of Bisphenol A

Abstract: The formation of gold nanoparticle (AuNP) composites with tantalum phthalocyanines (TaPc) complexes {1a and 1b (Figure 1)} is reported. The TaPc‐AuNPs conjugates were characterised by atomic force microscopy (AFM) and transmission electron microscopy. The AFM analyses show that conjugates of TaPc with AuNPs are more aggregated when compared to AuNPs alone. The conjugates and TaPc complexes were immobilized on a gold electrode by drop and dry method and these were characterized by electrochemical impedance spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Gracia et al [33] have reported the use of adsorbed AuNPs onto Au disk electrode where they observed no gold oxidation for AuNPs below 0.6 V on indium tin oxide (ITO) coated glass. Similarly, AuNPs do not show any gold oxidation on Au disk electrodes [9,34,35] below 0.6 V. The oxidation peak of AuNPs has been reported at 1.28 V (vs saturated calomel electrode) and the reduction peak at 0.81 V [33]. We reported the AuNP oxidation at 0.99 V in pH 7.4 buffer and the subsequent reduction at 0.36 V vs Ag|AgCl [9].…”
Section: Electrode Modification Using Mpcs and Their Conjugates With mentioning
confidence: 80%
See 4 more Smart Citations
“…Gracia et al [33] have reported the use of adsorbed AuNPs onto Au disk electrode where they observed no gold oxidation for AuNPs below 0.6 V on indium tin oxide (ITO) coated glass. Similarly, AuNPs do not show any gold oxidation on Au disk electrodes [9,34,35] below 0.6 V. The oxidation peak of AuNPs has been reported at 1.28 V (vs saturated calomel electrode) and the reduction peak at 0.81 V [33]. We reported the AuNP oxidation at 0.99 V in pH 7.4 buffer and the subsequent reduction at 0.36 V vs Ag|AgCl [9].…”
Section: Electrode Modification Using Mpcs and Their Conjugates With mentioning
confidence: 80%
“…pH 12 phosphate buffer solutions were prepared from KH 2 PO 4 and Na 2 HPO 4 , and NaOH was used to adjust the pH. Gold nanoparticles (and AuNP-MPc conjugates) were synthesised as described recently [9]. The synthesis of 4 ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations